Estimasi Debit Puncak Menggunakan Hidrograf Satuan Sintetik Pada Daerah Aliran Sungai Kayan Kabupaten Bulungan - Asta Asta; Nurjaya Nurjaya (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2019)
The Kayan Watershed in Bulungan Regency is the largest river in North Kalimantan which has the potential for flooding in several irrigated points. Kayan River is a flood-prone area and prioritized to be handled immediately because there is already a smooth life for the community. Potentially need to know the great potential of flooding in the Kayan River. To find out the relationship between flood discharge and flood time, the Synthetic Unit Hydrograph calculation method is used. The aim is to determine the shape and results of peak discharge in Synthetic Unit Hydrograph Y (SUH). This study uses a debit calculation in the Kayan watershed using Snyder HSS a nd Nakayasu HSS. From the calculation results obtained Snyder SUH peak discharge of 118.0 m3/ sec at 73.85 hours, and Nakayasu SUH has a peak discharge of 109.35 m3 / sec at 54.09 hours.